New Insight into the Concanavalin A-Induced Apoptosis in Hepatocyte of an Animal Model: Possible Involvement of Caspase-Independent Pathway - Xiangli Zhao; Cheng Fu; Lingjuan Sun; Hao Feng; Peiling Xie; Meng Wu; Xiaosheng Tan; Gang Chen (Molecules, 2023)
Concanavalin A (Con A) is known to be a T-cell mitogen and has been shown to induce hepatitis in mice through the triggering of conventional T cells and NKT cells. However, it remains unknown whether Con A itself can directly induce rapid hepatocyte death in the absence of a functional immune system. Here, by using an immunodeficient mouse model, we found Con A rapidly induced liver injury in vivo despite a lack of immunocyte involvement. We further observed in vitro that hepatocytes underwent a dose-dependent but caspase-independent apoptosis in response to Con A stimulation in vitro. Moreover, transcriptome RNA-sequencing analysis revealed that apoptosis pathways were activated in both our in vivo and in vitro models. We conclude that Con A can directly induce rapid but non-classical apoptosis in hepatocytes without the participation of immunocytes. These findings provide new insights into the mechanism of Con A-induced hepatitis.